Elucidating taxonomic problems of the genus Disparia Nagano, 1916 of Taiwan and its neighboring areas, with description of one new species (Lepidoptera, Notodontidae) - Wu, Shipher (Zootaxa, 2015)
The taxonomic problems of the genus Disparia Nagano, 1916 in Taiwan and its neighboring areas are elucidated in the present study. The hitherto well-known separated taxonomic units, Fentonia nigrofasciata Wileman, 1910 and Pseudofentonia medioalbida Nakamura, 1973, are confirmed as the conspecific species based on the type material examination. The latter is here treated as a junior synonym (syn. nov.). The taxon previously identified as “D. nigrofasciata” in most of studies is actually D. wilemani Matsumura, 1925 stat. rev. Fentonia variegata Wileman, 1910 is retained for the eastern Asian population as a subspecies of widespread D. diluta (Wileman, 1910) through comparison with other populations. In addition, one new species, D. kobayashii sp. nov., endemic to Taiwan is described. Including D. maculata (Moore, 1879), totally five Disparia species are distributed in Taiwan.